Effects of Rotor Eccentricity on Interior Permanent Magnet Motor Performance in Electric Vehicles - Ho, Truc Hoang; Chayopitak, Nattapon; Pupadubsin, Ruchao; Depaiwa, Nattawoot; Saito, Takushi (My University, 2025)
Interior Permanent Magnet (IPM) motors are a popular choice in electric vehicle (EV) powertrains because of their high efficiency, compact size, and controllability. Rotor eccentricity remains a significant challenge because it introduces unbalanced magnetic forces, which increase vibrations, noise, and the risk of premature motor failure. This study investigated the effects of static, dynamic, and mixed eccentricity on the performance of IPM motors and explored how numerical analysis can aid in fault detection during the design and diagnostic phases. This study aims to explore eccentricity fault conditions and their impacts on the motor torque, cogging torque, and magnetic flux density using Finite Element Analysis (FEA) with frequency spectrum analysis. The results show that three types of eccentricity being considered: static, dynamic, and mixed type, produce distinct harmonic signatures that significantly affect the motor's performance characteristics. Specific harmonic ranges are particularly sensitive to different fault types that provide key indicators for early fault detection.